The Psychological Impact of COVID-19 on Medical Students: A Cross-Sectional Study. - Pınar Daylan Koçkaya (Journal of Medical Education and Family Medicine)
Objective: The coronavirus disease 2019 (COVID-19) pandemic has intensified anxiety levels among medical students, who are predisposed to anxiety. Understanding the impact of the pandemic on future physicians is crucial for preparing medical education processes for potential future pandemics. This study aimed to assess pandemic-induced anxiety levels among medical students and their influence on their professional attitudes and to establish a theoretical framework for psychological interventions.Methods: This descriptive study surveyed 1,273 medical students from Terms 1 to 5 during the second semester of the 2020 academic year. Using an online platform via a distance education center, participants completed the Coronavirus Anxiety Scale (CAS) along with researcher-designed questions.Results: Among the participants, 51% were female and 49% male. Of these, 21.7% attained a score of ≥9 on the CAS, with 60.4% of those being female, representing a statistically significant disparity. Notably, 86.1% of the Term-1 students who lacked prior medical coursework had registered scores ≤8. Within Period 4, 29.1% surpassed the CAS threshold, indicating heightened anxiety compared with other periods. Families of students with CASs ≥9 presented a notably higher COVID-19 incidence rate, at 37.3%. During the pandemic, 31% of the students expressed apprehension regarding their chosen profession, with 46% surpassing the CAS threshold and 27% scoring ≤8.Conclusion: During the pandemic, 21.7% of the students experienced heightened anxiety, which was influenced by remote learning and family COVID-19 cases. The students who experienced anxiety questioned their professional path and considered changing their specialty. This highlights the need to prioritize protective measures and educational support for medical students during future crises.